2022
DOI: 10.1370/afm.2829
|View full text |Cite
|
Sign up to set email alerts
|

COPD Population in US Primary Care: Data From the Optimum Patient Care DARTNet Research Database and the Advancing the Patient Experience in COPD Registry

Abstract: PURPOSETo describe demographic and clinical characteristics of chronic obstructive pulmonary disease patients managed in US primary care. METHODSThis was an observational registry study using data from the Chronic Obstructive Pulmonary Disease (COPD) Optimum Patient Care DARTNet Research Database from which the Advancing the Patient Experience COPD registry is derived. Registry patients were aged ≥35 years at diagnosis. Electronic health record data were collected from both registries, supplemented with patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…One benchmark study identified patients at risk of recurrent asthma attacks using the Optimum Patient Care Research Database, identifying various predictors for attacks and evaluated them using logistic regression. The study resulted in the development of an online asthma risk prediction tool for research and clinical purposes [43][44][45]. However, this study only utilized logistic regression, which has been shown to be a poor classifier in cases of class imbalance.…”
Section: Plos Onementioning
confidence: 99%
“…One benchmark study identified patients at risk of recurrent asthma attacks using the Optimum Patient Care Research Database, identifying various predictors for attacks and evaluated them using logistic regression. The study resulted in the development of an online asthma risk prediction tool for research and clinical purposes [43][44][45]. However, this study only utilized logistic regression, which has been shown to be a poor classifier in cases of class imbalance.…”
Section: Plos Onementioning
confidence: 99%